Building clinical guidelines to promote cognitive defusion effectively: A partial and preliminary task analysis - Assaz, Daniel Afonso; Oshiro, Claudia Kami Bastos (Perspectivas em Análise do Comportamento, 2025)
Cognitive defusion is a central component of Acceptance and Commitment Therapy (ACT) that aims to reduce the control of the client’s thoughts over their behavior, when this is causing psychological suffering. Despite the fact that ACT literature is filled with procedures to promote cognitive defusion, to master these techniques is not sufficient to conduct an effective therapeutic process. Guidelines for clinical decision-making can aid therapists in becoming more effective in producing cognitive defusion, especially those without extensive experience. To this end, the methodology of a partial task analysis was used to, first, develop a rational model of sequential steps clients and therapists can proceed together in order to reach cognitive defusion. Then, three participants with Generalized Anxiety Disorder went through therapy sessions designed to promote cognitive defusion. Throughout the therapeutic processes, self-report questionnaires, in-session coded speech’s frequency and sequences and client and therapist qualitative reports were used as measures. These sets of empirical data were used to re-examine the rational model and construct a preliminary rational-empirical model that can offer clinical guidelines and inform therapeutic practice. Research limitations and further directions of research in refining the cognitive defusion task analysis are discussed